2016
DOI: 10.15835/nbha44210553
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Coffea arabica L. Zygotic Embryos by Vitrification

Abstract: As a consequence of the difficulty in conventional coffee seed storage, biotechnological alternatives such as cryopreservation have been investigated. The objective of this study was to develop a protocol for the cryopreservation of Coffea arabica L. (cv. 'Catuaí Vermelho' -IAC 144) zygotic embryos by vitrification. For the cryopreservation study, the embryos were immersed in Plant Vitrification Solution 2 at different times (0, 10, 25, 50, 100, and 250 min) and two temperatures (0 and 25 °C). Subsequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Pinto et al (2016) developed a protocol of cryopreserving coffee zygotic embryos using physical dehydration in silica gel, followed by osmotic rehydration after thawing. In another study, De Freitas et al (2016) demonstrated the successful cryopreservation and germination of zygotic embryos of Coffea arabica by immersing the zygotic embryos in plant vitrification solution. These findings provide the technical advancement achieved in cryopreservation of coffee germplasm.…”
Section: Evaluated Threementioning
confidence: 99%
“…Pinto et al (2016) developed a protocol of cryopreserving coffee zygotic embryos using physical dehydration in silica gel, followed by osmotic rehydration after thawing. In another study, De Freitas et al (2016) demonstrated the successful cryopreservation and germination of zygotic embryos of Coffea arabica by immersing the zygotic embryos in plant vitrification solution. These findings provide the technical advancement achieved in cryopreservation of coffee germplasm.…”
Section: Evaluated Threementioning
confidence: 99%
“…The dehydration process has to be sufficient to avoid the formation of ice crystals during the contact of the plant material with ultra-low temperatures. Therefore it is important to avoid the excessive water efflux, which can cause cell death during the dehydration process, and find the minimum of water needed to seedling formation takes place (Freitas et al, 2016).…”
Section: Cryopreservationmentioning
confidence: 99%
“…The critical tool for successful cryopreservation by vitrification is to induce tissue tolerance to dehydration with a highly concentrated vitrification solution [23]. Vitrification has been successfully used in the Coffea arabica zygotic embryo, and increased the germination rate (90%) after dehydration with plant vitrification solution 2 (PVS2) for 10 min at 0 • C before LN treatment [24]. LN treatment is linked with cryoinjury associated with stress-associated factors, such as the failure of tissue to tolerate dehydration and temperature.…”
Section: Introductionmentioning
confidence: 99%